"A sentencing": veteran educators' perceptions of a constriction of English learner students' opportunities across grade spans. Issue 3 (3rd July 2021) - Umansky, Ilana M.; Poza, Luis E.; Flores Gutierrez, Misael
ABSTRACT: Recent research suggests that English learner (EL) classification can impact students in both positive and negative ways. We do not know enough, however, about what contexts and features of EL education lead to these divergent effects. Because students are classified as ELs at all grade levels, and the structure and content of schooling change dramatically across grades, one important consideration is whether EL classification operates differently for students in different grade spans. This study draws on the knowledge of veteran EL educators in one large, urban school district to examine the affordances and potential hazards of being classified as EL in different grade spans. The paper asks first, how these educators interpret EL-classified students' academic and social experiences at different grade spans, and second, what features of schooling shape these heterogeneous experiences of EL classification. Analysis of in-depth interviews suggests that academic exclusion, insufficient resources, and tracking, among other schooling features, increasingly constrict opportunities for students classified as ELs in upper grade spans. Key transitions – from early to mid-elementary, and from elementary to secondary – also alter EL-classified students' experiences.